2020
DOI: 10.1002/edn3.129
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐scale environmental heterogeneity shapes fluvial fish communities as revealed by eDNA metabarcoding

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
49
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 110 publications
(166 reference statements)
5
49
0
Order By: Relevance
“…In aquatic ecosystems, several studies confirmed the positive relationships between eDNA concentration and abundance and/or biomass measured by quantitative PCR (speciesspecific DNA primers) as well as by eDNA metabarcoding (using multispecies DNA primers), both in the wild and in controlled conditions (Afzali et al, 2020;Boivin-Delisle et al, 2021;Doi et al, 2017;Evans et al, 2016;Hänfling et al, 2016;Kelly et al, 2014;Klobucar et al, 2017;Lacoursiere-Roussel et al, 2016;Maruyama et al, 2018;Pont et al, 2018;Shaw et al, 2016;Takahara et al, 2012;Thomsen et al, 2012Thomsen et al, , 2016Wilcox et al, 2016;Yates et al, 2020). Moreover, it has been shown that relationship between fish community structure and environment can be detected using eDNA metabarcoding and that sample replicates show high reproducibility (Afzali et al, 2020;Berger et al, 2020;Boivin-Delisle et al, 2021;Civade et al, 2016).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…In aquatic ecosystems, several studies confirmed the positive relationships between eDNA concentration and abundance and/or biomass measured by quantitative PCR (speciesspecific DNA primers) as well as by eDNA metabarcoding (using multispecies DNA primers), both in the wild and in controlled conditions (Afzali et al, 2020;Boivin-Delisle et al, 2021;Doi et al, 2017;Evans et al, 2016;Hänfling et al, 2016;Kelly et al, 2014;Klobucar et al, 2017;Lacoursiere-Roussel et al, 2016;Maruyama et al, 2018;Pont et al, 2018;Shaw et al, 2016;Takahara et al, 2012;Thomsen et al, 2012Thomsen et al, , 2016Wilcox et al, 2016;Yates et al, 2020). Moreover, it has been shown that relationship between fish community structure and environment can be detected using eDNA metabarcoding and that sample replicates show high reproducibility (Afzali et al, 2020;Berger et al, 2020;Boivin-Delisle et al, 2021;Civade et al, 2016).…”
mentioning
confidence: 79%
“…For each extraction batch, a negative extraction control was performed. The MiFish primers were used to target a hypervariable region of the 12S rRNA gene (174 bp) (Miya et al, 2015) and proved to be efficient to reliably document freshwater and marine fish communities from Q uébec (Afzali et al, 2020;Berger et al, 2020;Boivin-Delisle et al, 2021;Garcia-Machado…”
Section: Edna Extraction Pcr Amplification and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is increasing interest in this technique for characterizing fish diversity F I G U R E 1 Protocol of the step-by-step program comparisons. The comparison of each program (white boxes) is arranged sequentially according to the suite of steps in the OBITools pipeline (grey boxes) (Berger et al, 2020;Jerde et al, 2019;Juhel et al, 2020;McElroy et al, 2020;Sigsgaard et al, 2017) in particular when classical methods are too invasive or do not perform well, as is the case for rare species or those that inhabit the deep sea. Many primer pairs have been developed to amplify different mitochondrial DNA fragments of fish DNA.…”
mentioning
confidence: 99%
“…In addition to the above ten case studies conducted in various freshwater environments, MiFish eDNA metabarcoding methods have been applied to biodiversity monitoring in the Duck and Clinch Rivers, Tennessee, USA (Paine 2019); Lake Michigan, USA (Jurecki 2020); Jequitinhonha River catchment, Brazil (Sales et al 2020b); St. Laurence and Rupert Rivers, Canada (Boivin-Deslile et al 2020;Berger et al 2020); Lake Kasumigaura in Ibaraki, central Japan (Kondo et al 2016); agricultural waterway in Saitama, central Japan (Kimochi et al 2020); two rivers in Hokkaido and Hyogo, Japan (Akamatsu et al 2018); 14 rivers in Sado Island, Niigata, Japan (Koseki 2019); a small river in Okinawa, southern Japan (Sato et al 2018); an urban stream in Suwon City, Korea (Song et al 2019); four Korean rivers (Alam et al 2020); the middle and lower reaches of the Yangtze River, China (Nian et al 2020); and irrigation water from two agro-ecological regions of Sri Lanka (Gamage et al 2020). Furthermore, effects of seasonal thermal stratification and fish habitat preferences on the vertical distributions of eDNA were investigated in the Experimental Lakes Area, north-western Ontario, Canada (Littlefair et al 2020).…”
Section: Freshwater Fish Communitymentioning
confidence: 99%